Modeling for Determinants of Human Trafficking: An Empirical Analysis - Cho, Seo-Young (Social Inclusion, 2015)
This study aims to identify robust push and pull factors of human trafficking. I test for the robustness of 70 push and 63 pull factors suggested in the literature. In doing so, I employ an extreme bound analysis, running more than two million regressions with all possible combinations of variables for up to 153 countries during the period of 1995–2010. My results show that crime prevalence robustly explains human trafficking both in destination and origin countries. Income level also has a robust impact, suggesting that the cause of human trafficking shares that of economic migration. Law enforcement matters more in origin countries than destination countries. Interestingly, a very low level of gender equality may have constraining effects on human trafficking outflow, possibly because gender discrimination limits female mobility that is necessary for the occurrence of human trafficking.